2012
DOI: 10.4236/jbise.2012.59061
|View full text |Cite
|
Sign up to set email alerts
|

Air plasma for medical applications

Abstract: The design and the electric and emission characteristics of two handheld air plasma spray generators are presented. The plasma is generated by 60 Hz periodic discharges between two concentrically cylindrical electrodes. A ring magnet is used to rotate arc discharges, which sprays outward by an air flow. The rotation of arc discharges keeps the generated plasma in non-equilibrium state and at relatively low temperature (<55°C). The plasma effluent yet contains high energy electrons which dissociate molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Atmospheric pressure plasmas, used in medical applications, can be generated by various electric discharges [1] [2] [3] [4]; however, plasmas have to be generated in a non-equilibrium state, so that the electron kinetic energy, gained from the electric source, is better used for producing reactive species, rather than for heating the plasma effluent; keeping plasma in low temperature. The reactive species carried by the plasma effluent can trigger biochemical reactions, which furnish biocidal effects for sterilization applications, speed up coagulation cascade for hemostasis applications, and promote wound healing [5]- [15].…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric pressure plasmas, used in medical applications, can be generated by various electric discharges [1] [2] [3] [4]; however, plasmas have to be generated in a non-equilibrium state, so that the electron kinetic energy, gained from the electric source, is better used for producing reactive species, rather than for heating the plasma effluent; keeping plasma in low temperature. The reactive species carried by the plasma effluent can trigger biochemical reactions, which furnish biocidal effects for sterilization applications, speed up coagulation cascade for hemostasis applications, and promote wound healing [5]- [15].…”
Section: Introductionmentioning
confidence: 99%
“…One such plasma generator [11] implements airflow and magnetic field to rotate elongated arc discharges. It functions as a blood coagulator by using atomic oxygen, carried in the plasma effluent to activate erythrocyte-platelet interactions, to stop blood bleeding from external wounds [12]. Chen et al [13] and Kuo et al [14] showed that this air plasma spray, carrying significant amount of atomic oxygen, could clot anti-coagulated whole blood samples in less than 20 seconds, which is much less than 30 minutes for an untreated sample to reach complete coagulation.…”
Section: Introductionmentioning
confidence: 99%
“…From these backgrounds, recently studies on the application of a nonthermal atmospheric pressure plasma to blood coagulation have been attracting special attentions as an alternative to thermal cauterization methods because it causes little damage to human tissue. [6][7][8][9][10][11][12] Hereafter, medical equipment using a low temperature nonthermal atmospheric pressure plasma is called a low energy ionized gas coagulation equipment (LE-IGCE). Fridmann et al 9 observed blood clot formation using a floating electrode dielectric barrier discharge (DBD) plasma without visible or microscopic tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…Fridmann et al 9 observed blood clot formation using a floating electrode dielectric barrier discharge (DBD) plasma without visible or microscopic tissue damage. Kuo et al 10,11 tested a nonthermal air plasma spray that produces plasma at relatively low temperatures below 55°C as an LE-IGCE for blood coagulation. Choi et al 12 developed a 900 MHz atmospheric pressure argon plasma jet with low temperature below 47°C and studied the acceleration of blood coagulation.…”
Section: Introductionmentioning
confidence: 99%